Control of pervasive row crop weeds with dicamba and glufosinate applied alone, mixed, or sequentially. (24th October 2022) - Jones, Eric A. L.; Leon, Ramon G.; Everman, Wesley J.
Abstract: Dicamba and glufosinate are among the few effective postemergence herbicides to control multiple herbicide-resistant weeds in southeastern U.S. cotton and soybean production. Field studies were conducted to determine the effect of weed size and the application of dicamba and glufosinate individually, mixed, or sequentially on common ragweed, goosegrass, large crabgrass, ivyleaf morningglory, Palmer amaranth, and sicklepod control. Sequential herbicide treatments were applied 7 d after the initial treatment. The tested weeds sizes predominantly did not affect weed control. Control of broadleaf weed species with sequential herbicide applications never increased compared to the initial herbicide application. Two applications of glufosinate and/or dicamba + glufosinate controlled grasses better than one application. The order of the herbicides in the sequential applications did not affect broadleaf species control, whereas herbicide order was important for the control of grass weeds. Grass weed control was higher when glufosinate was applied before dicamba. Dicamba + glufosinate additively controlled the weeds, except for goosegrass, for which control was less for dicamba + glufosinate compared to glufosinate alone. The results of the experiment provide evidence that dicamba and glufosinate applied individually, mixed, and sequentially are effective on common row crop weeds found in the southeastern United States, but the species present may dictate how the herbicides are applied together.